Effects of Levodopa-Carbidopa Intestinal Gel Compared with Optimized Medical Treatment on Nonmotor Symptoms in Advanced Parkinson's Disease: INSIGHTS Study. (4th November 2022) - Chung, Sun Ju; Calopa, Matilde; Ceravolo, Maria G.; Tambasco, Nicola; Antonini, Angelo; Chaudhuri, K. Ray; Robieson, Weining Z.; Sánchez-Soliño, Olga; Zadikoff, Cindy; Jin, Man; Barbato, Luigi M.
Abstract : Background . Nonmotor symptoms (NMS) are common in advanced Parkinson's disease (APD) and reduce health-related quality of life. Objective . The aim of the study was to evaluate levodopa-carbidopa intestinal gel (LCIG) versus optimized medical treatment (OMT) on NMS in APD. Methods . INSIGHTS was a phase 3b, open-label, randomized, multicenter study in patients with APD (LCIG or OMT, 26 weeks) (NCT02549092). Primary outcomes assessed were total NMS (NMS scale (NMSS) and PD sleep scale (PDSS-2)). Key secondary outcomes included the Unified PD Rating Scale (UPDRS) Part II, Clinical Global Impression of Change (CGI-C), and PD Questionnaire-8 (PDQ-8). Additional secondary measures of Patient Global Impression of Change (PGIC), King's PD Pain Scale (KPPS), and Parkinson Anxiety Scale (PAS) also were evaluated. Finally, safety was assessed. Results . Out of 89 patients randomized, 87 were included in the analysis (LCIG, n  = 43; OMT, n  = 44). There were no significant differences in NMSS or PDSS-2 total score changes (baseline to Week 26) between LCIG and OMT; within-group changes were significant for NMSS (LCIG, p < 0.001 ; OMT, p = 0.005 ) and PDSS-2 (LCIG, p < 0.001 ; OMT, p < 0.001 ). Between-group treatment differences were nominally significant for UPDRS Part II (p = 0.006 ) and CGI-C (p < 0.001 ) at Week 26 in favor of LCIG; however, statistical significance could not be claimed in light of primary efficacy outcomes. PGIC (Week 26) and KPPS (Week 12) scores were nominally significantly reduced with LCIG versus OMT (p < 0.001 ; p < 0.05 ). There were no significant differences in PDQ-8 or PAS. Adverse events (AEs) were mostly mild to moderate; common serious AEs were pneumoperitoneum ( n  = 2) and stoma-site infection ( n  = 2) (LCIG). Conclusions . There were no significant differences between LCIG versus OMT in NMSS or PDSS-2; both LCIG and OMT groups significantly improved from baseline. AEs were consistent with the known safety profile.